(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
– Finite element analysis software, ABAQUS was used effectively in analyzing the stress – strain behavior under the application of static wheel load in the modeled flexible pavement structure. A series of 30 pavement response models were analyzed. In elasto – plastic analysis, rutting values were used to find the Traffic Benefit Ratio (TBR) for reinforced sections. TBR value ranges from 1.01 to 2.16. Multiple linear regression models were developed with acceptable degree of accuracy. Field studies were conducted on unreinforced and coir geotextile reinforced sections to evaluate the benefits of coir geotextiles in flexible pavements.